The Effect of Distance Learning on Computer Vision Syndrome Complaints In Students Of The Faculty of Medicine Yarsi University Class 2020 and Its Review According to the Islamic View - Muhammad Ariq Yudia; Atiek Indriawati; Toto Heriyanto (Junior Medical Journal, 2023)
Computer Vision Syndrome (CVS) is a group of eye and vision-related symptoms caused by prolonged use of computers, tablets, e-readers and mobile phones that cause increased stress on near vision. In the Covid-19 pandemic situation, a Muslim must make various efforts to prevent the spread of the plague. Among the efforts is to keep a distance, one example is Distance Learning. The purpose of this study was to determine the effect of distance learning on CVS complaints in YARSI University Medical Faculty students Batch 2020 and its review according to Islamic view. The type of research is descriptive observational with a cross-sectional research design. Questionnaires are distributed via google form. The research was conducted on YARSI University Medical Faculty Students Class 2020 with a total sample of 137 respondents. Data analysis was carried out univariately using SPSS ver. 25. Based on the results of the study, distance learning has an effect on CVS complaints in YARSI University Medical Faculty Students Class 2020. There is an increase in the incidence of CVS when doing distance learning based on gender, computer use, distance learning duration 6 hours a day, blinking frequency 10 times/minute, bad lighting, antiglare use, eye-to-computer distance 50 cm, monitor position above eyes, manual brightness adjustment, and negative polarity. To conclude, there is influence from distance learning on CVS complaints based on individual factors, environmental factors, and computer factors.